2014
DOI: 10.3109/03008207.2014.959118
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical compression upregulates MMP9 through SMAD3 but not SMAD2 modulation in hypertrophic scar fibroblasts

Abstract: These results demonstrate that compressive stress upregulates MMP9 by SMAD3 but not by SMAD2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Pathological cutaneous wound healing resulting in excessive scarring and fibrosis is the consequence of an imbalance between ECM synthesis by myofibroblasts and degradation and remodeling by MMPs ( 13 ). We found that remodeling marker MMP-9 was increased after mechanical stress, which was also observed by other groups ( 58 60 ). VEGF is an important promoter of angiogenesis and therefore microvessel density might be increased by mechanical tension.…”
Section: Discussionsupporting
confidence: 89%
“…Pathological cutaneous wound healing resulting in excessive scarring and fibrosis is the consequence of an imbalance between ECM synthesis by myofibroblasts and degradation and remodeling by MMPs ( 13 ). We found that remodeling marker MMP-9 was increased after mechanical stress, which was also observed by other groups ( 58 60 ). VEGF is an important promoter of angiogenesis and therefore microvessel density might be increased by mechanical tension.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, fibroblasts have been reported to degrade fibrin clots by generating MMPs and their inhibitors (TIMPs), leading to a disorder of matrix formation and degradation (49). The enhanced expression levels of MMP-2 and MMP-9 have been shown to be associated with decreased levels of collagen I and collagen III in HS tissues (50). In this study, we found that TGF-β1 significantly increased the MMP-2 and MMP-9 expression at the transcriptional and translational levels.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical strain is a known inducer of ECM remodeling in a number of tissues and organs, such as skin, 15 lung tissue, 11,16 bone, 17 and vascular systems. 18 Alterations include cell reorientation, matrix composition, collagen, and elastin realignment.…”
Section: Discussionmentioning
confidence: 99%